Internalisasi Nilai-Nilai Demokrasi Pada Proses Pembelajaran PAI - Indana, Nurul; Mustofa, Ali; Hidayat, Fahmil (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
PAI learning that incorporates democratic values is conscious and planned learning to create active learning that is critical of the surrounding environment, namely the family, school, and community. This article aims to describe the implementation of the internalization of democratic values in the Islamic Religious Education learning process in class XI IPA IV at SMA Negeri 3 Jombang. This research is descriptive and qualitative in nature, with data collected through observation, interviews, and documentation. The analysis technique uses the stages of reduction, data display, and data verification. The research aims to provide as accurate a picture as possible of the internalization of democratic values in the learning process and to identify the supporting and inhibiting factors (constraints) in the learning process. The results of the research and analysis of the research data show that the internalization of democratic values in the PAI learning process can be realized through teachers becoming role models for students, socializing democratic values, schools supporting, assisting, and facilitating students, being fair, building emotional bonds between students to create good social values, providing a sense of comfort, involving students, teachers' abilities in their respective fields, facilities and infrastructure, family support, school culture, limited learning time that is not in line with the large amount of material, the indirect influence of social media on children's personalities, and a lack of motivation to learn among students.